(untitled) (AYUSHDHARA, 2017)
Concept of promoting health and preventing diseases through nutrition and special nutritional preparations has been used for millennia in Ayurveda. The concept of promotion of health through Rasayanas is based on Ayurveda pathophysiology and its understanding of health and physiological system imbalances that lead to disease development. The word Rasayana is composed of 2 words ‘Ras’ + ‘Ayan’. The means by which one gets the excellence of Rasa (The nourishing fluid which is produced immediately after digestion) is Rasayana. These Rasa nourishes our body & stimulates the immunity of the body & keeps us healthy. The term Rasayana connotes a specific meaning ‘Drugs, diet + regimens’ which promote longevity by delaying aging & preventing diseases are called Rasayana. Impairment of circulation of this body fluids results in disease and decay. This ancient understanding is being re-introduced as “Nutraceuticals”. The word is a portmanteau of nutrition and pharmaceutical and refers to the extracts of foods claimed to have a medicinal effects on human health (Defelice 2002). In order to bring a parlance among the two concepts and better understanding of the Ayurvedic concept, an comparative analysis of both the concepts has been done.